2012
DOI: 10.1038/nrneph.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the pool of deceased donor organs for kidney transplantation

Abstract: Expanding the pool of available deceased donor kidneys is critical for improving the outcomes of prospective and current renal transplant candidates. A number of interventions have been proposed that may increase the pool of donors in the US. However, these interventions have variable levels of empirical evidence supporting their potential beneficial impact. Proposed interventions include the instigation of policies for presumed donor consent, the expansion of donor registration, increased quality oversight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 86 publications
0
21
0
1
Order By: Relevance
“…Thus, even optimal consent practices in the ICU, while valuable, will be insufficient to completely solve the problem of organ scarcity. Potential ways to narrow this gap include: a) increased utilization of non-standard organs, such as from DCDDs (2226); b) paying living donors to increase the number of living donor transplants(27); or c) using simulation and Markov models to examine the efficiency and societal implications of different allocation strategies. (28–30) Despite recent laudable efforts in the social media arena to increase the number of people - especially the 18–39 year cohort - enrolling in donor registries, these OPTN/UNOS data demonstrate that such efforts alone will not bridge the organ supply-demand gap, given that over 30,000 patients are added to the kidney transplant waitlist each year.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even optimal consent practices in the ICU, while valuable, will be insufficient to completely solve the problem of organ scarcity. Potential ways to narrow this gap include: a) increased utilization of non-standard organs, such as from DCDDs (2226); b) paying living donors to increase the number of living donor transplants(27); or c) using simulation and Markov models to examine the efficiency and societal implications of different allocation strategies. (28–30) Despite recent laudable efforts in the social media arena to increase the number of people - especially the 18–39 year cohort - enrolling in donor registries, these OPTN/UNOS data demonstrate that such efforts alone will not bridge the organ supply-demand gap, given that over 30,000 patients are added to the kidney transplant waitlist each year.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 Interventional studies have demonstrated successful approaches to encouraging organ donor registration and organ donation itself. 16 These practices could improve the supply of pediatric-quality kidneys. Alternatively, the OPTN could develop policy proposals to promote greater equity in the allocation of pediatric-quality kidneys to children.…”
Section: Discussionmentioning
confidence: 99%
“…The allograft shortage prolongs waiting list times, resulting in deteriorations in health and quality of life for patients maintained on chronic dialysis. To expand organ supplies, we increasingly utilize kidneys from deceased donors with risk factors for allograft dysfunction (e.g., older age, high terminal serum creatinine) (2)(3)(4). However, the procurement of kidneys with possible injury along with the lack of precise tools to characterize that injury have led to high organ discard rates and increasing numbers of recipients with long-term allograft dysfunction (5,6).…”
Section: Introductionmentioning
confidence: 99%